2021
DOI: 10.17977/um048v27i2p58-63
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Flipped Classroom in Improving Students' Writing Skills at The University of Brawijaya

Abstract: This study aims to investigate the effect of the flipped classroom on students' writing skills, active involvement in the classroom, and students' perception of flipped classrooms. By using a pre-experimental design, this study involved 27 fourth-semester students of Class B, Educational English Department of the Faculty of Cultural Studies, University of Brawijaya Malang, in the academic year 2019-2020. The participants were selected through cluster random techniques. The data were collected from pretest and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…The results of his research concluded that using the teaching factory model could produce quality vocational graduates who were ready to enter the world of work. So is research results(Arya Sadewa et al, 2019) (Arya Sadewa et al, 2019 associated with the Knowledge Management System indicate that to create professionalism in the form of competence, educational institutions must apply the concept of the knowledge management system, and results of research conducted (Siswanto, 2021) related to the use of the Flipped Classroom learning model showed that students' writing skills improved and helped students become more active in online self-study. Students also showed positive perceptions of flipped classrooms in improving writing skills.…”
Section: The Effectiveness Of the Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of his research concluded that using the teaching factory model could produce quality vocational graduates who were ready to enter the world of work. So is research results(Arya Sadewa et al, 2019) (Arya Sadewa et al, 2019 associated with the Knowledge Management System indicate that to create professionalism in the form of competence, educational institutions must apply the concept of the knowledge management system, and results of research conducted (Siswanto, 2021) related to the use of the Flipped Classroom learning model showed that students' writing skills improved and helped students become more active in online self-study. Students also showed positive perceptions of flipped classrooms in improving writing skills.…”
Section: The Effectiveness Of the Test Resultsmentioning
confidence: 99%
“…Teaching factory learning, also known as industrial activity-based learning, is a method for bridging the competency gap between classroom knowledge and real-world settings provided by schools and industrial needs (Kuswantoro, 2014). In this regard, efforts are needed to design a Teaching Factory learning model that is collaborated with the application of information technology 21st-century competencies in answering the challenges of needs in the Industrial Revolution 4.0 era and one of the models used is the Teaching Factory model based on the Flipped Classroom Knowledge Management System at SMK as a form of effort to synchronize school learning with the industrial world (Siswanto, 2021) (Anggraeni, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Model flipped classroom dianggap model yang tepat diterapkan dalam pembelajaran menulis proposal kegiatan. Penggunaan model flipped classroom memberikan kesempatan yang lebih banyak kepada siswa untuk bereksplorasi dalam memahami konten (Siswanto, 2021). Model pembelajaran tersebut merupakan model pembelajaran inovatif yang memanfaatkan teknologi dan peningkatan keterlibatan siswa pada proses pembelajaran (Suo & Hou, 2017).…”
Section: A Pendahuluanunclassified
“…Life skills education inserted into chemistry subjects is often called Chemoentrepreneurship (CEP). CEP is an approach/method used in Chemistry learning by inserting entrepreneurship related to Chemistry material (Dewi & Mashami, 2019;Zia Ulhaq et al, 2021;Wijayati & Rengga, 2009). Entrepreneurship that is inserted in Chemistry lessons starts from product manufacturing planning to product marketing (Prayitno et al, 2020).…”
Section: Introductionmentioning
confidence: 99%